PENGARUH KESADARAN MEREK, PERSEPSI KUALITAS, DAN ASOSIASI MEREK TERHADAP KEPUTUSAN PEMBELIAN MELALUI EKUITAS MEREK (STUDI PADA MAHASISWA PENGGUNA SMARTPHONE BLACKBERRY DI UNIVERSITAS DIPONEGORO SEMARANG) - Sofa Marwati; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2014)
This research motivated by communication technology growth that supplier make as a business chance. One of products that competed by supplier now is smartphone. Smartphone be a communication technology that considered can make the user be easier. Specially, this research tell about Blackberry smartphone which is already be a leader smartphone on Top Brand Index (TBI) in Indonesia since 2011 until 2013.. Goal of this research is to know what influence of brand awareness, perceived  quality, brand association to purchase decision through brand equity of Blackberry. The type of this research is explanatory, with data collecting technique by questionnaire and interview. The sampling technique of this research use multi stage sampling and purposive sampling. The amount of sample is 96 people. This research is use qualitative and quantitative analysis technique (validity test, reliability test, correlation coefficient, simple and multiple regeression analysis, the coefficient of determination, a significant test (t and F) and path analysis). The result of this research is all of independent variable which is brand awareness (X1) perceived quality (X2), brand association (X3) simultaneously or partially can influence dependent variable which is brand eqiuty (Y1) and purchase decision variable (Y2). According the result of path analysis, direct influence on brand awareness variable to purchase decision is more than indirect influence, and perceived quality variable and brand association to purchase decision direct influence less than indirect influence.